Respons Labu Madu (Cucurbita moschata Dusrch) terhadap Zat Pengatur Tumbuh Alami berbagai Dosis - Fitri Kurniati; Ida Hodiyah; Tedi Hartoyo; Indra Nurfalah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
The purpose of the research was to studied the response of honey pumpkin (Cucurbita moschata Durch) to the kind of natural PGRs substances in various dosages.The research was conducted at the Greenhouse of griculture Faculty Siliwangi University since April 2017 until September 2017, by ecperiment method using Randomized Block Design, 9 treatments, i.e., b0: control, b1: onion bulb 200 ml, b2: onion bulb 300 ml, b3: bamboo shoots 200 ml, b4: bamboo shoots 300 ml, b5: banana 200 ml, banana b6: banana 300 ml, b7: mix (onion bulb + bamboo shoots + banana) 200 ml, b8: mix (onion bulb + bamboo shoots + banana) 300 ml. Each of treatmnent replicated three times. The parameters analyzed were plant height, number of leaves, leaf area, plant dry weight, fruit weight per plant, fruits weight per pieces, fruit length, and fruit diameter. The results showed that honey pumpkin gave the same response to the natural PGRs with various dosages on plant height, number of leaves, plant dry weight, fruit weight, fruit length, and fruit diameter. But, honey pumpkin gave the different response on the leaves area and fruit weight per plant. The largest leaves was found by giving extract of banana bulb of 300 ml (7119.8 cm2) and the mixture extract (onion bulb + bamboo shoots + banana bulb) of 300 ml (6978.5 cm2). The highest of fruit weight per plant is in extract of bamboo shoots 300 ml (388.6 g), and extract of banana bulb 300 ml (347.6 g).